Rola rolnictwa i przemysłu spożywczego w zaspokajaniu popytu pośredniego i końcowego - Mrówczyńska-Kamińska, Aldona (The Importance of Agriculture and Food Industry in Meeting Indirect and Final Demand, 2006)
The aim of the paper is to show the importance of agriculture and food industry in meeting indirect and final demand. Agricultural products' supply is intended mainly for an indirect consumption. Apart from self-supply, agriculture is an important raw material supplier for alimentary industry and other country's economy branches. The rest, the least part of the supply is intended for a final demand which is composed mainly of household consumption.The economic development initialised a significant self-supply increase in food industry of material supply. The significance of agriculture in this scope was diminished. Food industry products' supply is intended mainly for a final demand which is composed mainly of household consumption. The rest of supply is intended for an indirect consummation mainly of food industry.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 149-156